Divorce Rates Better Predict Population‐Level Reproductive Success in Little Penguins Than Foraging Behaviour or Environmental Factors - Matthew D. Simpson; Ashton L. Dickerson; Andre Chiaradia; Lloyd Davis; Richard D. Reina (Ecology and Evolution)
ABSTRACT Understanding the relative contributions of environmental, behavioural and social factors to reproductive success is crucial for predicting population dynamics of seabirds. However, these factors are often studied in isolation, limiting our ability to evaluate their combined influence. This study investigates how marine environmental variables, foraging behaviour and social factors (divorce), influence reproductive success in little penguins (Eudyptula minor) over 13 breeding seasons. By examining these factors together, we aimed to identify which is the most reliable predictor of population‐level reproductive success. We found that divorce rate was the most consistent predictor of reproductive success, with lower annual rates of divorce preceding the breeding season associated with higher hatching and fledging success. Foraging trip duration also influenced reproductive success, but in contrasting ways: Longer trips during egg incubation were linked with increased hatching success, while shorter trips after hatching led to higher fledging success. Marine environmental conditions had unexpected effects, with a lower Southern Oscillation Index (SOI) correlating with improved hatching and fledging success, in contrast to previous research, while sea surface temperature (SST) had no significant effect on reproductive success. This highlights the complexity of seabird breeding responses to large‐scale oceanographic indices, suggesting SOI and SST are generally less reliable measures to use as indicators of reproductive success. Our results suggest that divorce rate could serve as a valuable, noninvasive index of reproductive success in seabirds.